Analysis of degradation of motor oils used in ZETOR tractors - Sejkorová, Marie; Glos, Josef (My University, 2017)
The durability of motor oil and then the change interval are influenced by numerous factors and it is not easy to determine optimal mileage for a specific means of transport or a machine. The manufacturer proposes a maximum limit, but it is not always suitable since operating conditions influence the process significantly. Using FTIR spectrometry and analytical ferrography methods we evaluated used motor oils collected from older types of ZETOR tractors. Change intervals were extended for most tested oil fills. The analysis results showed that when the tractors were exposed to a considerable everyday load during autumn tasks, the lubrication and friction processes in their motors were affected negatively which resulted in increased wear. Therefore it is not advisable to extend the change interval as proposed by the ZETOR manufacturer.
Analýza motorových olejů provozovaných v traktorech Zetor
Keywords: tractors; motor oil; analysis; degradation; particles; FTIR spektrometry; ferrography.; traktory; motorový olej; analýza; degradace; částice; FTIR spektrometrie